Evaluation of Gola River annual discharge: An Experience of Spring Fed Siwalik Mountain River - R. K. Pande (Faculty of Geography, Universitas Gadjah Mada, 1986)
The stream character as such and its discharge behavior are the gross results of a range of events and functions of nature. The word 'stream flow', as used in the present text, is referred to 'catchment yield'. This yield is obviously discharge, q, which has dimensions of volume, L3, and time, T, expressed here onwards in cumec (one cubic metre per second) which will ultimately be converted into a single voluminous unit litre (1) and hence referred to as Q. As the_ Gola River is a spring fed river,, its discharge behaviour is absolutely dependent on the sub-surface flow of Siwalik Ranges. It has been noticed that the sub-surface flow fluctuates according to the monsoonal and non-monsoonal precipitation intensity. Hence, an interesting seasonal rhythm is noticed in the monsoonal and non-monsoonal discharge with the changing values of stream magnitude and velocity.",